Investigating the Painted Pottery Traditions of the First Millennium BC Northwestern Arabia and Southern Levant: Contexts of Discovery and Painted Decorative Motives - Tebes, Juan Manuel (2015)
This is the second article of two studies investigating the Iron Age painted pottery traditions of the Northern Hejaz and Southern Levant: the Qurayyah/Midianite pottery; Taymanite/Sana’iye pottery; Edomite/Busayra Painted Ware/Southern Transjordanian-Negev Pottery (STNP); and al-‘Ula/Khuraybah pottery. The first article focused on the chronology, geographical distribution and Arabian parallels of these painted ceramics according to the latest archaeological researches in the area (Tebes 2013). In this article, I will study their archaeological contexts of discovery, painted decorative motives and iconography